2015
DOI: 10.5993/ajhb.39.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness and Substance Use Problems in Relation to Homelessness Onset

Abstract: Serious mental illness and sedative problems may characterize homeless youth who are vulnerable to adulthood homelessness, although longitudinal cohort studies are needed to explicate temporal relations between variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…However, less is known about differences in sexual risk behaviors according to current age (i.e., young adults vs. older adults) as many studies of homeless youth do not compare youth to older adults in the same sample. Less is known as well about the age of homelessness onset as a potential, independent risk factor despite findings suggesting that age of onset is correlated with other risk behaviors such as substance use, with a younger age at the onset of homelessness being associated with a higher incidence of substance use [ 36 ]. An Oakland, California based study found that, among homeless adults >50 years old, those who first became homeless before age 50 reported higher rates of substance use than those with a later age of homelessness onset [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, less is known about differences in sexual risk behaviors according to current age (i.e., young adults vs. older adults) as many studies of homeless youth do not compare youth to older adults in the same sample. Less is known as well about the age of homelessness onset as a potential, independent risk factor despite findings suggesting that age of onset is correlated with other risk behaviors such as substance use, with a younger age at the onset of homelessness being associated with a higher incidence of substance use [ 36 ]. An Oakland, California based study found that, among homeless adults >50 years old, those who first became homeless before age 50 reported higher rates of substance use than those with a later age of homelessness onset [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The age at homelessness onset and the duration of homelessness are also related to increased drug use among homeless adults. The rate of drug use is higher in those who first experience homelessness before age 25 and increases as the duration of homelessness increases (9,10). Wenzel et al (2010) suggested that a longer duration of homelessness provides added time to form social networks with a greater density of drug using peers (11).…”
Section: Introductionmentioning
confidence: 99%
“…Homelessness (living without stable, safe, permanent, appropriate housing, or the immediate prospect, means and ability of acquiring it(1)) is detrimental for almost every life dimension of affected individuals. Being homeless is a crucial stress factor for well-being as it re ects severe material deprivation, and in addition erodes mental, cognitive and physical health (2)(3)(4)(5)(6)(7)(8), exposes individuals to risky conditions and behaviors (e.g., violence, bad meteorological conditions, discrimination) (8-10), and precludes access to such basic services as sanitation, health care, water or food. (11)(12)(13) Access to food is a consistent unmet need of homeless populations.…”
Section: Introductionmentioning
confidence: 99%